Istashirni Mobile application for depression diagnostic using machine learning - BELFAR, YOUCEF; AL ABDALLAH, AHMAD; Supervisor : SAOUDI, LALIA (FACULTY: MATHIMATICS AND COMPUTER SCIENCE DEPARTEMENT: COMPUTER SCIENCE - OPTION : RTIC, 2021)
Depression has become the disease of the times and has spread widely in the world, where its spread has led to a decrease in the effectiveness of individuals in society and prompted many people to contemplate suicide. Many modern methods and techniques have been used to diagnose depression and guide patients to recover from the disease. In this project we designed an application that aims to identify people with depression. Determining the type of depression using machine learning techniques, where a comparison is made between the specific characteristics of each disease and the data entered by each patient, and as a result, the case is diagnosed and the type of depression is determined. The experimental results obtained have proven the effectiveness of our application.
Keywords: Depression diagnosis , E-mental health, Machine learning, depression ,smartphone-based CBT for depression.